Young Lives Qualitative Research: Round 1 - Peru - Ames, P; Rojas, V; Portugal, T (Young Lives, 2009)
This report presents an initial analysis of some of the qualitative data collected in four of the 20 Young Lives sites in Peru between August and December 2007. Data collection was carried out with both cohorts of Young Lives children (the Younger Cohort are aged 5/6 and the Older Cohort are aged 11/13), as well as their caregivers, teachers, community representatives and other children. The sub-sample includes 51 children. The three overriding questions that guided the qualitative research are: (1) what are the key transitions in children’s lives, how are they experienced (particularly in relation to activities, relationship, identities, and well-being) and what influences these experiences? (2) How is children’s well-being understood and evaluated by children, caregivers and other stakeholders? What shapes these different understandings, and what causes them to change? What do children, caregivers and other stakeholders identify as sources of and threats to well-being, and what protective processes can enable children to minimize these threats? (3) How do policies, programmes and services shape children’s transitions and well-being? What are the different stakeholder perspectives on these processes? What is the interplay between public, private and not-for-profit sectors and communities within these processes? The qualitative research entailed a mix of methods to generate data on the themes of transitions, well-being and services , including individual interviews with children, caregivers and teachers, and group interviews with children (both cohorts), as well as with adults in the community. Creative methods such as drawing and neighbourhood walks with the children were used as a basis of discussion of key research themes. Semi-structured observations of homes, schools and community settings provided the context for analyzing and understanding the data.